Relationship between Self Management and Self Efficacy Towards Quality of Life in Type 2 Diabetes Mellitus Patients: Systematic Review - Rohematus Soleha; Abdul Muhith; Siti Nur Hasina (GLOBAL HEALTH SCIENCE GROUP, 2025)
The implementation of self-management for diabetes mellitus patients is influenced by various factors, one of which is a lack of self-confidence ( self-efficacy ) regarding disease and health resulting in people not behaving in accordance with health values ​​​​and not having a good quality of life. The aim of writing this systematic review is to determine the relationship between self-management and efficacy on the quality of life in diabetes mellitus patients. The method used is a literature search with systematic review (PRISMA) as the standard for conducting a systematic review. Search articles using several journal databases, namely Google Scholar, Science Direct, and Clinicalkey, spanning a period of 5 years (2020-2024) with the keywords